Pharmacodynamic and pharmacokinetic behavior of landiolol during dobutamine challenge in healthy adults - Krumpl, Günther; Ulč, Ivan; Trebs, Michaela; Kadlecová, Pavla; Hodisch, Juri (BMC pharmacology & toxicology, 2020)
BACKGROUND: To study the pharmacokinetic and -dynamic behavior of landiolol in the presence of dobutamine in healthy subjects of European ancestry. METHODS: We conducted a single-center, prospective randomized study in 16 healthy subjects each receiving an infusion of dobutamine sufficient to increase heart rate by 30 bpm followed by a 60 min infusion of 10 μg/kg/min landiolol. RESULTS: Dobutamine-induced increases in heart rate were stable for at least 20 min before a 60 min landiolol- infusion was started. The dobutamine effects were rapidly antagonized by landiolol within 16 min. A further slight decrease in heart rate during 20-60 min of the landiolol infusion occurred as well. Upon termination of landiolol infusion, heart rate and blood pressure recovered rapidly in response to the persisting dobutamine infusion but did not return to the maximum values before landiolol infusion. The pharmacokinetic parameters of landiolol in presence of dobutamine showed a short half-life (3.5 min) and a low distribution volume (0.3 l/kg). No serious adverse events were observed. CONCLUSION: Landiolol can antagonize the dobutamine-induced increases in heart rate and blood pressure in a fast way. A rapid bradycardic effect until steady-state plasma levels is followed by a slow heart rate reduction. The latter can be attributed to an early desensitization to dobutamine. Consequently, after termination of landiolol, the heart rate did not achieve maximum pre-landiolol values. The pharmacokinetics of landiolol during dobutamine infusion are similar when compared to short- and long-term data in Caucasian subjects. Landiolol in the given dose can thus serve as an antagonist of dobutamine-induced cardiac effects. TRIAL REGISTRATION: Registration number 2010-023311-34 at the EU Clinical Trials Register, registration date 2010-12-21.
Keywords: Morpholines; morfoliny; dospělí; Dobutamine; Healthy Volunteers; dobutamin; Female; klinické křížové studie; kardiotonika; beta blokátory; intravenózní infuze; močovina; Adult; mladý dospělý; ženské pohlaví; Urea; zdraví dobrovolníci pro lékařské studie; lidé; dvojitá slepá metoda; Cross-Over Studies; krevní tlak; srdeční frekvence; prospektivní studie; Double-Blind Method; Male; Prospective Studies; Infusions, Intravenous; Young Adult; Cardiotonic Agents; Adrenergic beta-Antagonists; mužské pohlaví; Blood Pressure; Heart Rate; Humans